2019
DOI: 10.1002/ps.5531
|View full text |Cite
|
Sign up to set email alerts
|

Dwarf‐cashew resistance to whitefly (Aleurodicus cocois) linked to morphological and histochemical characteristics of leaves

Abstract: BACKGROUND: The cashew whitefly (CW), Aleurodicus cocois, is an important pest of cashew in Brazil. The use of resistant plants may be an effective strategy for the control of this pest. In a preliminary assay, we found that dwarf-cashew clones show different levels of resistance to CW. Here, we hypothesized that such resistance is associated with morphological characteristics of cashew leaves and their content of phenolic compounds. RESULTS: We determined (i) the attractiveness and suitability for oviposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Holland and Fahrig (2000) and Mignon et al (2002) have shown that field borders can have a significant influence on insect abundance and diversity. There could also be the effect of the cashew tree's induced defences (Boone et al 2011;Goiana et al 2019), as it was observed that most of the cashew trees that were attacked in the first year of observation were no longer attacked in the second year. Agboton et al (2017) had made the same observation.…”
Section: Discussionmentioning
confidence: 99%
“…Holland and Fahrig (2000) and Mignon et al (2002) have shown that field borders can have a significant influence on insect abundance and diversity. There could also be the effect of the cashew tree's induced defences (Boone et al 2011;Goiana et al 2019), as it was observed that most of the cashew trees that were attacked in the first year of observation were no longer attacked in the second year. Agboton et al (2017) had made the same observation.…”
Section: Discussionmentioning
confidence: 99%
“…Plants of the F 2 generation had bigger and thicker leaves and significantly thicker layers of palisade and spongy mesophyll than triploids of the F 1 generation and parental lines of B. oleracea and B. napus, whereas FC320 F 2 had a compact mesophyll structure with small intercellular spaces. The leaf surface and leaf morphological characteristics may affect their resistance to infestation by insect herbivores [51][52][53]. Marasek-Ciolakowska et al [53] showed that reduced infestation by the cabbage whitefly (Aleyrodes proletella) on leaves of resistant cultivars of kale and savoy cabbage was related to the structure of the epidermis, thickness of the lamina, and compactness of the mesophyll.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical factors such as allelochemicals, proteins, and several metabolites are often associated with the morphological structures of species like trichomes, mesoderm, and parenchyma, among many other [4][5][6]. The introgression of genes from wild species has been shown to be the main alternative for tomato breeding programs, as there are several records of resistance in relation to arthropod pest species in this crop [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%